2009
DOI: 10.1523/jneurosci.5247-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Prostaglandin E2Synthesis Interacts in a Temporally Supplementary Sequence with Constitutive Prostaglandin-Synthesizing Enzymes in Creating the Hypothalamic–Pituitary–Adrenal Axis Response to Immune Challenge

Abstract: Inflammation-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis has been suggested to depend on prostaglandins, but the prostaglandin species and the prostaglandin-synthesizing enzymes that are responsible have not been fully identified. Here, we examined HPA axis activation in mice after genetic deletion or pharmacological inhibition of prostaglandin E 2 -synthesizing enzymes, including cyclooxygenase-1 (Cox-1), Cox-2, and microsomal prostaglandin E synthase-1 (mPGES-1). After immune challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 62 publications
8
65
2
1
Order By: Relevance
“…Observations in mPGES-1 KO mice, which cannot evoke PGE2 synthesis upon immune challenge (Engblom et al, 2003;Engström et al, 2012), have shown that the induced PGE2 synthesis is involved in the stress hormone release in response to immune insults (Elander et al, 2009), and the present data are consistent with the idea that this PGE2 synthesis occurs in brain endothelial cells. It should be noted however, that this involvement may apply only to the later phases of the stress hormone response, because the immediately occurring corticosterone release, at least when LPS is used as immune stimulus, is unaffected by mPGES-1 deletion (Elander et al, 2009) and seems to be driven by a Cox-1 and not a Cox-2 dependent mechanism (Elander et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Observations in mPGES-1 KO mice, which cannot evoke PGE2 synthesis upon immune challenge (Engblom et al, 2003;Engström et al, 2012), have shown that the induced PGE2 synthesis is involved in the stress hormone release in response to immune insults (Elander et al, 2009), and the present data are consistent with the idea that this PGE2 synthesis occurs in brain endothelial cells. It should be noted however, that this involvement may apply only to the later phases of the stress hormone response, because the immediately occurring corticosterone release, at least when LPS is used as immune stimulus, is unaffected by mPGES-1 deletion (Elander et al, 2009) and seems to be driven by a Cox-1 and not a Cox-2 dependent mechanism (Elander et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…These observations have bearing on the interpretation of the present data on induced c-Fos expression in the PVH, suggestive of activation of hypophysiotropic cells in this nucleus. While we here found that the IL-1β induced c-Fos expression in the PVH was dependent on IL-1R1s on non-hematopoietic cells, this observation does not necessarily imply that the IL-1β signaling that give rise to this response occurs via endothelial cells and induced PGE2 synthesis, because c-Fos expression in PVH upon immune challenge with intraperitoneally injected LPS has been shown to be unaffected by genetic deletion of the prostaglandin synthesizing enzymes Cox-1, Cox-2 and mPGES-1 (Elander et al, 2009). In the work with endothelial specific IL-1R1 knockdown it was shown that such knockdown abolished c-Fos expression in the PVH after intravenous but not after intraperitoneal injection of IL-1β, suggesting a PGE2 dependent pathway for the immune signaling after the former but not after the latter administration route (Ching et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations